2017
DOI: 10.1186/s40529-017-0189-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bio-fertilizer containing beneficial fungi and rhizospheric bacteria on health promoting compounds and antioxidant activity of Spinacia oleracea L.

Abstract: BackgroundThis study evaluates the influences of bio fertilizers containing mycorrhizal fungi (Glomus fasciculatum, Glomus mosseae) individually or in combination with N-fixer (Azotobacter chroococcum), K solubilizer (Bacillus mucilaginous) and P solubilizer (Bacillus megaterium) on soil fertility and phytochemical levels of spinach.ResultsRoot colonization by mycorrhizal fungi was increased in the presence of bacterial inoculation in comparison to individual inoculation treatments. Inoculation of bio fertiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 51 publications
2
28
1
1
Order By: Relevance
“…The treatment with AMF showed photosynthetic pigment contents in lettuce leaves similar to the control. In our study, although the application of AMF did not show a positive effect on the pigment contents, some previous studies indicated that AMF induces accumulation of those pigments in some leafy vegetables such as lettuce (Baslam et al 2011) and spinach (Khalid et al 2017).…”
Section: The Content Of Photosynthetic Pigmentscontrasting
confidence: 86%
“…The treatment with AMF showed photosynthetic pigment contents in lettuce leaves similar to the control. In our study, although the application of AMF did not show a positive effect on the pigment contents, some previous studies indicated that AMF induces accumulation of those pigments in some leafy vegetables such as lettuce (Baslam et al 2011) and spinach (Khalid et al 2017).…”
Section: The Content Of Photosynthetic Pigmentscontrasting
confidence: 86%
“…Substantial contribution of Biofertilizer in sustainable maintenance of human health has been reported. Biofertilizers improve the nutritious properties of fresh vegetables by increasing; the antioxidant activity, the total phenolic compounds and chlorophyll ( Khalid et al, 2017 ). Spinach inoculated with different biofertilizers was found to have 58.72 and 51.43% higher total phenolic content than the un-inoculated control ( Khalid et al, 2017 ).…”
Section: Contribution Of Microbial Inoculant In Sustainable Maintenanmentioning
confidence: 99%
“…Augmented the concentrations of total phenolic compounds, flavonoids, and phenolic acids [34] Co-inoculation increased fruit production, fruit size, and concentrations of sugars and ascorbic and folic acids [35] Phyllobacterium endophyticum PEPV15 Rhizospheric bacterium Fruit Improved vitamin C level and yield [36] Paenibacillus polymyxa RC05 Rhizospheric bacterium Fruit Improved vitamin C level and yield [37] Bacillus simplex RC19 Rhizospheric bacterium Fruit Improved vitamin C level and yield [38] Pseudomonas sp. 5Vm1K Rhizospheric bacterium Fruit Improved vitamin C level [35] Tomato Rhizophagus irregularis, Funneliformis mosseae Arbuscular mycorrhizal fungus Fruit…”
Section: Arbuscular Mycorrhizal Fungi and Rhizospheric Bacteria Leafmentioning
confidence: 99%